A Randomized Interventional Study of Traditional Versus Patency Documented Haemostasis for Prevention of Radial Artery Occlusion After Transradial Catheterization - P. Desai, Arpan; Bhagarhatta, Rajeev (Journal of Hypertension and Cardiology, 2016)
Objective: The objective of this study was to evaluate the efficacy of patent haemostasis in avoiding radial artery occlusion after transradial catheterization. Background: Radial artery occlusion is an infrequent but discouraging complication of transradial access. It is related to factors such as sheath to artery ratio and is less common in patients receiving heparin. Despite being clinically silent in most cases, it limits future transradial access. Patients and Methods: 130 patients undergoing transradial catheterization were prospectively enrolled in the study. 65 patients were randomized to group I, and underwent conventional pressure application for haemostasis. 65 were randomized to group II and underwent pressure application confirming radial artery patency using Barbeau’s test. Radial artery patency was studied at 24 hr and 30 days using Barbeau’s test. Results: There was Statistically significant difference found in rate of radial artery occlusion of both the groups at 24 hours (24.61% vs. 4.61% ,X2(1)=4.44, P<0.05) and at 30 days(20% vs. 3%,X2(1) =4.03, P < 0.05). Patients with Higher age and smaller radial artery diameter were at significantly higher risk of radial artery occlusion. No other procedural variables were found to be associated with radial artery occlusion. Conclusion: Patent haemostasis is highly effective in reducing radial artery occlusion after radial access and guided compression should be performed to maintain radial artery patency at the time of haemostasis, to prevent future radial artery occlusion.
Keywords: Radial Artery Occlusion; Transradial Catheterization; Patent Haemostasis; Haemostasis; Transradial Access